2014
DOI: 10.1111/iji.12148
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the TNFα, TNFR1 gene and risk of rheumatoid arthritis in Chinese Han population

Abstract: Recent advances have highlighted a major genetic contribution to the pathogenesis of rheumatoid arthritis (RA).The aim of this study was to investigate whether polymorphisms of TNF-α (rs1800630, rs1800629) and TNFR1 (rs767455) were associated with susceptibility to and clinical outcome of RA in Chinese Han population. The target gene polymorphisms were genotyped in 256 patients with RA and 331 healthy controls using a high resolution melting (HRM) method. ESR, CRP, RF anti-CCP and anti-GPI level were also assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Various methods have been reported to determine the genotype of TNF-α -308G/A, such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) (Sun et al, 2013), restriction fragment length polymorphism (RFLP) (Manolova et al, 2014), and high resolution melting (HRM) (Li et al, 2014). However, the accuracy of these methods as genotyping has rarely been verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been reported to determine the genotype of TNF-α -308G/A, such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) (Sun et al, 2013), restriction fragment length polymorphism (RFLP) (Manolova et al, 2014), and high resolution melting (HRM) (Li et al, 2014). However, the accuracy of these methods as genotyping has rarely been verified.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also indicated that TNF-α -308G/A polymorphisms were not associated with susceptibility to RA. Li et al reported that the rs1800629 A allele of TNF-α was negatively associated with RA in the Chinese population (Li et al, 2014). But several studies have concluded that TNF-α -308G/A polymorphisms were not associated with RA susceptibility (Sun et al, 2013;Manolova et al, 2014;Cadena-Sandoval et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It affects females 2-4 times more frequency than males and affects up to 1% of adults worldwide (Song et al, 2013). The precise etiology of RA has not been determined, but many studies support an important role for genetic factors in RA susceptibility and progression (Kim et al, 2010;Li et al, 2014;MacGregor et al, 2000). The susceptibility to RA is influenced by major genetic components such as the human leukocyte antigen (HLA) complex, where multiple alleles of the DRbeta1 chain that share a common epitope in the third hypervariable region determine disease susceptibility and severity.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate genes studies have found polymorphic genetic variants to be associated with chronic diseases, such as fibromyalgia (FERNÁNDES-DE-LAS-PENAS et al, 2012;, arthritis LI et al, 2014;SONG et al, 2014;ZHANG et al, 2014), periodontitis BRAOSI et al, 2012;CLAUDINO et al, 2012) and also TMD (DIATCHENKO et al, 2005;MELOTO et al, 2011;MICHELOTTI et al, 2014). Most studies are focusing on genes that are able to influence the activity of peripheral afferent pain fibers, central nervous system pain processing and activity of peripheral cells that release proinflammatory mediators and the production of proinflammatory mediators from cells within the central nervous system .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, if a more representative group of individuals with TMJ disorders were included, statistical association would probably be found for this variable. High concentrations of TNF-α have been found in the plasma, synovial fluid and tissue of patients with reumathoid arthritis (RA) 68 and TNF-α polymorphism has also been associated with this disease69,70 . Although RA and TMD are distinct pathologies, both present with chronic characteristics and may share some genetic susceptibility.…”
mentioning
confidence: 99%